DAMPAK PERAYAAN EKARISTI KAMPUS BAGI PERKEMBANGAN IMAN MAHASISWA STKIP WIDYA YUWANA - Musta Wakit; Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2021)
Humans have desire to live and relate intimately with God. The realization of the attitude to be more intimate with God can be achieved through spiritual activities such as personal prayer, devotion, meditation and especially the Eucharistic celebration. There is no other Church's activities that has the meaning more than the Eucharistic celebration. It is because in the Eucharistic Celebration, there is a celebration of the events of God's people living together in Christ. Eucharistic celebration is one of development’s benchmark of the faith church members. This research was conducted to answer the main question, which is: How can the Eucharistic Celebration develop the faith? The qualitative method was used in this research and the respondents were the 2nd to the 14th semester students of STKIP Widya Yuwana in 2018/2019 academic year. Respondents, in this research, were 10 students. This study aims to analyze the impact of the campus’ Eucharistic celebration toward the students of STKIP Widya Yuwana’s faith development. As the result of this research, 8 respondents (80%) stated that the Eucharistic celebration held on campus had an impact to their faith development, although 3 respondents (30%) stated that the Eucharistic Celebration had no impact towards the faith development. Next, there were 5 respondents (50%) who stated that the students lacked respect for the Eucharistic celebration, so that, it didn't have any impact on their faith development, although 3 respondents (30%) found that the Eucharistic Celebration held on campus had impact to faith development. So, there are 3 respondents (30%) who stated that the Eucharistic Celebration held on campus had an impact to their faith development and also said that the Eucharistic Celebration held on campus had no impact to their faith development.